2013
DOI: 10.5688/ajpe77227
|View full text |Cite
|
Sign up to set email alerts
|

Factors That Influence Student Completion of Course and Faculty Evaluations

Abstract: Objective. To determine if there is a relationship between students' grades, gender, age, or ethnicity and their completion of course and/or faculty evaluations. Methods. Data were collected and analyzed for relationships among students' gender, age, ethnicity, and course grade on their completion rates of course and faculty evaluations.Results. The grade a student received in a course was not related to completion rates for course or faculty evaluations. Students born in 1987 or earlier were significantly mor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
14
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 6 publications
2
14
0
1
Order By: Relevance
“…Our study shows that even student ratings based on a validated evaluation sheet are comparable to evaluations created by peers using the same metric. We confirmed that the bias in student evaluations as emphasized in the literature [29–31] can be minimized using a validated questionnaire and reviewer training. The training does not need to be longer than an hour.…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…Our study shows that even student ratings based on a validated evaluation sheet are comparable to evaluations created by peers using the same metric. We confirmed that the bias in student evaluations as emphasized in the literature [29–31] can be minimized using a validated questionnaire and reviewer training. The training does not need to be longer than an hour.…”
Section: Discussionsupporting
confidence: 79%
“…Thus, their feedback is critical. On the other hand, student’s evaluations are influenced by many factors that cannot be influenced by the lecturer and lecture’s quality including age [29], expected grades in the relating tests [30], intrinsic motivation or general interest in the topic [31]. In fact, the lecture rating by students is often influenced by how entertaining the lecture is.…”
Section: Introductionmentioning
confidence: 99%
“…One of the reasons why non-tenure and part-time faculty members may tend to be more lenient on grading or more willing to dilute course content is due in part to student evaluations. Student evaluations are an integral part of how faculty are evaluated and influence changes to the curriculum and faculty performance (Hatfield & Coyle, 2013). Research suggests that grade inflation and coursework deflation are a result of a heavy reliance on student evaluations (Ali & Ajmi, 2013).…”
Section: Evaluation Of Findings and Implicationsmentioning
confidence: 99%
“…In spite of these differences, the researchers found that neither students nor faculty desired the elimination of student evaluations of instruction. Hatfield and Coyle (2012) examined the likelihood that students would complete a course evaluation of a faculty's instruction. Their research indicated that course grades did not influence the likelihood of completing a faculty evaluation.…”
Section: Introductionmentioning
confidence: 99%